PENGARUH MEDIA AUDIOVISUAL TERHADAP TINGKAT PENGETAHUAN SISWA DALAM PEMBELAJARAN RENANG DI SMPN 6 KARAWANG BARAT - Farid Alka Riana, Ahmad; Suryana Nasution, Nana; Nurwansyah Sumarsono, Rhama; Zinat Achmad, Irfan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem in this study emerged when the researcher carried out the Independent MBKM FKIP Teaching Program. At that time, the physical education teachers at SMP Negeri 6 Karawang Barat conducted swimming learning activities. After the students completed the learning session, during the evaluation and question-and-answer session, the students still did not understand swimming techniques. Therefore, the researcher chose the title “The Effect of Audiovisual Media on Students’ Knowledge Levels in Swimming Learning at SMPN 6 Karawang Barat.” This study aims to determine the effect of audiovisual media on students’ knowledge levels in swimming learning at SMPN 6 Karawang Barat.This study used an experimental method with a one-group pretest-posttest design. The results of this study showed that there was an effect of using audiovisual media on students’ knowledge levels in swimming learning at SMPN 6 Karawang Barat. These results were indicated by the hypothesis test results with a significance value of 0.000. Since the result of 0.000 is less than 0.005, it can be concluded that the use of audiovisual media has a significant effect on students’ knowledge levels in swimming learning at SMPN 6 Karawang Barat.